THE ROLE OF GREEN TECHNOLOGIES IN SOLVING ENVIRONMENTAL PROBLEMS - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This article examines the role of green technologies in solving modern environmental problems. In the context of global climate change, environmental degradation, and resource depletion, green technologies have become essential tools for achieving sustainable development. The study analyzes key areas of green technology application, including renewable energy, waste management, water conservation, and sustainable agriculture. It also highlights the environmental, economic, and social benefits of these technologies, as well as the challenges associated with their implementation. Furthermore, the paper discusses global trends and emphasizes the importance of integrating green innovations into national development strategies. The findings suggest that green technologies play a crucial role in reducing environmental impact and ensuring a sustainable future.